Analysis of the Role of Madrasah Heads in Improving the Timeliness of Student Attendance - Putri Lestari; Mamlukhah (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2026)
This research is motivated by the discovery of late student attendance, which affects learning effectiveness and the culture of madrasah discipline. The purpose of the study was to analyze the role of madrasah heads in improving the timeliness of student attendance and to identify leadership strategies for building on-time attendance discipline. The research uses a descriptive, qualitative approach with a case study design in one madrasah. Data was collected through in-depth interviews with madrasah heads and related parties, observations of attendance discipline, and a review of policy documents and attendance recaps. The analysis is carried out through data reduction, presentation, and the drawing of conclusions. The results of the study show that the increase in timeliness is driven by a combination of consistent rulemaking, strengthening the culture of discipline through example, routine supervision, coordination with homeroom teachers and BK teachers, and the implementation of a monitoring and follow-up system, including coaching, awards, and educational sanctions. The research clarifies the leadership mechanism of madrasah heads in discipline management and provides practical implications for the formulation of more measurable, collaborative, and sustainable attendance policies.